The Current Situation of Neurological Health in Bangladesh: A Perspective - Mst. Mohona Khatun; Mohammad Shahangir Biswas; Suronjit Kumar Roy; Md Foyzur Rahman; Rubait Hasan; Syed Masudur Rahman Dewan; Munna Kumar Podder (Health Science Reports)
ABSTRACT Background and Aims In Bangladesh, neurological disorders are becoming a bigger public health concern because they significantly increase disability, mortality, and medical costs. This review explores the current neurological health landscape in Bangladesh, with a focus on prevalent disorders such as stroke, epilepsy, Parkinson's disease, and meningitis. Methods To complete this review, we retrieved pertinent information from published articles that we located in Google Scholar, PubMed, and Scopus. We looked up terms like meningitis, stroke, Parkinson's disease, epilepsy, and neurological disease. Results Due to common risk factors like diabetes, high blood pressure, and lifestyle choices, the prevalence of these conditions is increasing. Inadequate healthcare infrastructure, especially in rural areas, and a lack of specialized medical care make diagnosis and treatment extremely difficult. Effective disease management is made more difficult by systemic flaws in the public health system and socioeconomic disparities. Conclusion Public education campaigns, preventive measures, better access to necessary medications, and improvements to the healthcare infrastructure are all vital to lessen this burden. To improve neurological health outcomes in Bangladesh, this review emphasizes the urgent need for focused interventions and strong policies. It also emphasizes the significance of ongoing research and medical advancements in managing and lowering the prevalence of major neurological disorders in Bangladesh.